2010
DOI: 10.1007/s00436-010-1831-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the sensitivity of microtubules of Giardia lamblia to the herbicide oryzalin

Abstract: Giardia lamblia is a protozoan that inhabits the small intestine of vertebrates, attaching to the epithelial cells by means of cytoskeletal elements. G. lamblia trophozoites possess several microtubular structures, namely the adhesive disc, the median body, the funis and the four pairs of flagella. Several drugs that target cytoskeletal proteins have been used in the study of cytoskeletal function and dynamics. In this work, we used oryzalin, which binds to alpha-tubulin, as a tool to study the Giardia cytoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Something similar occurs with the nematode model Caenorhabditis elegans and in mammalian cell lines, where cytotoxic activities have been observed at IC 50 values greater than 25 and 50 μM, respectively. 4 , 5 , 9 , 34 , 35 In agreement with the conclusions made by Terra et al 11 and Hirst et al, 33 G. intestinalis , C. elegans , and mammals could be considered ORY-non-susceptible organisms.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Something similar occurs with the nematode model Caenorhabditis elegans and in mammalian cell lines, where cytotoxic activities have been observed at IC 50 values greater than 25 and 50 μM, respectively. 4 , 5 , 9 , 34 , 35 In agreement with the conclusions made by Terra et al 11 and Hirst et al, 33 G. intestinalis , C. elegans , and mammals could be considered ORY-non-susceptible organisms.…”
Section: Resultssupporting
confidence: 84%
“… 32 Similarly, treatment with dinitroaniline derivatives has shown microtubule disruption activity in protozoa with low half-maximal inhibitory concentrations (IC 50 ). T. gondii (IC 50 = 0.1 μM), 4 P. falciparum (IC 50 = 3.9 μM), 33 and L. mexicana (IC 50 < 20 μM) 7 , 11 are some of the most relevant ORY-susceptible protozoan parasites. A previous study suggested that the protozoan Giardia intestinalis was also susceptible to ORY treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 50 and 100 µM, most of the protozoa were killed. Morphological studies showed curling of the flagella in about 60% of the cells, elongation of the median body (i.e., a structure made of microtubules), changes in the shape of the cell, and blockage of cell division (Figures 1-3) [27]. …”
Section: Anaerobic Protozoamentioning
confidence: 99%